Cu2O/hollow mesoporous silica composites for the rapid and efficient removal of methylene blue. Issue 17 (28th July 2020) - Wang, Jingjing; Xiao, Wei; Teng, Hongni; Yin, Huimin; Chen, Xiaoping; Jiang, Xianjing; Huo, Chengqian; Teng, Maohao; Ma, Shuhua; Al-Haimi, Akram Ali Nasser Mansoor
ABSTRACT: Cu2 O/hollow mesoporous silica (HMS) composite was synthesized using HMS as supporting material by the impregnation method. This composite displayed integrated physicochemical performance of Cu2 O and HMS, resulting in low density, large surface area and excellent dispersibility. The synthesized nano-sized composite of Cu2 O/HMS demonstrated rapid and effective removal for methylene blue with an efficiency of 99.8% with the reaction time of 5 min. Moreover, the Cu2 O/HMS composite exhibited high stability and present no obvious performance degradation after seven cycles. The dye removal efficiency stood up to 89% even after 15 cycles. The improved properties of Cu2 O/HMS are possibly the account of the collaborative effect between the mesoporous adsorption with Cu2 O photocatalysis. GRAPHICAL ABSTRACT: